please solve this question lesson is polynomial
Attachments:
![](https://hi-static.z-dn.net/files/d6d/7d16662bfca9dd17a429a5cdaef5af03.jpg)
Answers
Answered by
1
Step-by-step explanation:
(VI) Here, the factors of 5 are +/-1 and +/-5.
Using hit and trial, take the factor to be x + 1.
x + 1 = 0
So, x = -1.
Substituting the value of x in the equation,
= (-1)^3 - (3*-1^2) - (9*-1) - 5
= -1 - 3 + 9 - 5
= 0
So, x + 1 is a factor of the equation.
Now, (x^3) - (3x^2) - (9x) - (5) can be divided by (x + 1) to get the factors
Answered by
0
1ST QUESTION ANSWER
BY FACTORISATION
Attachments:
![](https://hi-static.z-dn.net/files/d9b/b759f49cb4d51b18da96dbfbb664a3a5.jpg)
Similar questions